In children with severe acute malnutrition, is there a relationship between adherence to hospital discharge criteria and the rates of relapse thereafter - Burnett, Georgia Kirsten (Stellenbosch : Stellenbosch University, 2025)
Thesis (MNutr)--Stellenbosch University, 2024.